Switchable 10, 20, and 30 GHz region photonics-based microwave generation using thulium-doped fluoride fiber laser - Ahmad, Nurul Atiqah; Dahlan, Samsul Haimi; Cholan, Noran Azizan; Ahmad, Harith; Zian, Cheak Tiu (Optica Publishing Group, 2018)
In this work, switchable 10, 20, and 30 GHz region photonics-based microwave generation in a fiber laser cavity is proposed and demonstrated. The microwave generation is based on the beating of a dual-wavelength thuliumdoped fluoride fiber laser. With the aid of a micro-air gap in an adapter, single, double, and triple Brillouin spacing can be generated in a single fiber laser cavity without re-routing the cavity. The wavelength spacing of the dual wavelengths that are induced by the single, double, and triple Brillouin spacing are 0.084, 0.166, and 0.254 nm, respectively, at a center wavelength of 1490 nm. In addition, a numerical calculation is performed using MATLAB to prove the generation of microwave signals at 11.34, 22.44, and 34.3 GHz. With the advantage of switchability among the 10, 20, and 30 GHz regions, the proposed photonics-based microwave generation is promising for the advancement of 5G technologies.